The Effect of Substrate Concentration and Bacterial Loading on Biobutanol Production from Molasses Using Clostridium acetobutylicum - Zahra Dzaki Roofia Putri; Azel Destyano; Ni Ketut Sari; Nurul Widji Triana; Sintha Soraya Santi (G-Tech: Jurnal Teknologi Terapan, 2026)
Biobutanol is a promising alternative fuel due to its high energy content and compatibility with existing fuel infrastructure. This study evaluates the effects of molasses substrate concentration and Clostridium acetobutylicum loading on biobutanol production via the Acetone–Butanol–Ethanol (ABE) fermentation process. Molasses concentration was varied at 3%, 4%, 5%, 6%, and 7%, while bacterial loading ranged at 1%, 2%, 3%, 4%, and 5%. Fermentation was performed under anaerobic conditions at 37 °C for 4 days with CaCO₃ as a buffering agent. Unlike previous studies that investigated these parameters individually, this work examines their combined influence using a statistical optimization approach. The highest experimental biobutanol concentration of 6.06% was obtained at a substrate concentration of 6% and a bacterial loading of 5%. Optimization using Response Surface Methodology (RSM) produced a statistically significant quadratic model (p < 0.0001) with good predictive performance (R² = 0.9045; predicted R² = 0.8153). The optimal conditions were predicted at a substrate concentration of 5.220% and a bacterial loading of 4.580%, yielding a biobutanol concentration of 6.087%. These results highlight the importance of simultaneous parameter optimization for improving molasses-based biobutanol production.